Enforcement of Law Against Violations of Dedicated Bus Rapid Transit (BRT) Lanes in the Legal Systems of Indonesia and the United States - Daniel Tambunan; Handoyo Prasetyo (Universitas Islam Sultan Agung, 2026)
This article examines the legal framework and law enforcement mechanisms addressing violations of exclusive Bus Rapid Transit (BRT) lanes, with a primary focus on the TransJakarta system in Indonesia and a comparative perspective with practices in Minneapolis and Austin, United States. The misuse of dedicated BRT lanes by unauthorized vehicles remains a persistent urban transport problem that undermines service efficiency, travel time reliability, and public trust in mass transportation systems. Despite the existence of clear legal norms, weak compliance and inconsistent enforcement continue to challenge the effectiveness of BRT operations. This research applies a normative juridical method using statutory and comparative approaches. Primary legal materials include national traffic and transportation laws, regional regulations of the Jakarta Provincial Government, and municipal ordinances in selected U.S. cities. Secondary legal materials consist of academic journals, policy reports, and official government publications related to public transportation and traffic law enforcement. The findings indicate that Indonesia relies heavily on a centralized regulatory framework supported by police enforcement and electronic traffic law enforcement (ETLE), while enforcement consistency and technological coverage remain limited. In contrast, cities in the United States emphasize localized regulation, automated enforcement systems, and administrative sanctions designed to create a deterrent effect. This study concludes that strengthening inter-agency coordination, expanding evidence-based automated enforcement, harmonizing sanctions between national and local regulations, and enhancing public legal awareness are essential to improving compliance and ensuring the sustainability of BRT systems as a backbone of urban mobility.